2023
DOI: 10.3390/ani13223578
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of High-Quality Brazilian Beef Production: A Comparative Life Cycle Assessment of Premium and Super-Premium Beef

Henrique Biasotto Morais,
Luis Artur Loyola Chardulo,
Welder Angelo Baldassini
et al.

Abstract: When individual purchasing power increases in society, there is a trend toward a quantitative and qualitative increase in the consumption of products. Considering the magnitude of beef production in Brazil, environmental impacts are important factors for the domestic and international markets. This study assessed a Brazilian feedlot system characterized by high animal welfare standards that produces high-quality beef that is more marbled than that produced in grass-fed systems. We assessed the environmental im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…More specific studies get into the assessment of product quality in special confinement systems, reflecting the trend toward qualitative consumption of products, as indicated by Morais et al [ 74 ]. In their study, they concluded values of 5.03, 4.77, and 8.89 kg of CO 2 eq./kg of live weight gain in confinement for premium, super-premium Angus, and super-premium Wagyu meats, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…More specific studies get into the assessment of product quality in special confinement systems, reflecting the trend toward qualitative consumption of products, as indicated by Morais et al [ 74 ]. In their study, they concluded values of 5.03, 4.77, and 8.89 kg of CO 2 eq./kg of live weight gain in confinement for premium, super-premium Angus, and super-premium Wagyu meats, respectively.…”
Section: Methodsmentioning
confidence: 99%